Research on the Effect of Engine Intake System and Cylinders with Different Surface Shapes on the Engine - XU, Changchun; Muk Cho, Haeng (International Journal of Engineering and Technology, 2018)
In the present, the automobile is the popular tool in every family. In the DI diesel engine, about the intake system that this system can af-fect properties of the engine, such as change the air flow velocity and pressure into cylinders, and among the air through the pump or throttle body(throttle valve), the throttle body can make air to produce eddies and change the air flow pressure, because when air into cylinder, the air pressure is an important parameter, so the time of the throttle valve opening in very important(also say the angle of opening), we know the surface of the cylinder can affect the air and fuel mixing rate, so we have investigated the effect of different surface shape. Found the different surface can improve the engine combustion properties. In this article, we will combine the throttle valve and the different surface shapes of the cylinder, make a survey what find the effect of this combination at the constant revolutions per minute(RPM). We will set the velocity at 1000rpm by tentative and investigate the position of the piston at the same location(inhale status) when premix air and fuel into the cylinder.Â